A modified two-dimensional sensory organization test that assesses both anteroposterior and mediolateral postural control - Wagner, Andrew R.; Merfeld, Daniel M. (Frontiers in Rehabilitation Sciences, 2023)
Background: The Sensory Organization Test (SOT) was designed to measure changes in postural control in response to unreliable visual and/or proprioceptive feedback. However, secondary to the manipulation of sensory cues in only the sagittal plane, the SOT is capably of only describing postural control in a single direction. The present study aimed to characterize postural responses to a modified SOT designed to concurrently challenge both anteroposterior and mediolateral postural control. Methods: Twenty-one healthy adult volunteers (30.6±10.2 years) completed the standard anteroposterior one-dimensional (1D) SOT, in addition to a modified SOT with the support surface sway referenced to both anteroposterior and mediolateral postural sway (two-dimensional, 2D). Our primary analysis concerned a comparison of mediolateral, as well as anteroposterior postural sway measured during the standard one-dimensional (i.e., pitch tilt) and the novel two-dimensional (i.e., roll and pitch tilt) sway referenced paradigms. Here, postural sway was quantified by calculating the root mean square distance (RMSD) of the center of pressure (CoP) during each trial. Results: Our data showed that the 2D sway referenced conditions yielded a selective increase in mediolateral postural sway relative to the standard 1D conditions for both wide (2 = 0.66) and narrow (2 = 0.78) stance conditions, with anteroposterior postural sway being largely unaffected (2 = 0.001 to 0.103, respectively). The ratio between mediolateral postural sway in the sway referenced conditions and postural sway in the corresponding stable support surface conditions was greater for the 2D (2.99 to 6.26 times greater) compared to 1D paradigms (1.25 to 1.84 times greater), consistent with a superior degradation of viable proprioceptive feedback in the 2D paradigm. Conclusion: A modified 2D version of the SOT was shown to provide a greater challenge to mediolateral postural control relative to the standard 1D SOT protocol, putatively as a result of a superior capacity to degrade proprioceptive feedback in the mediolateral direction. Given these positive findings, future studies should investigate the clinical utility of this modified SOT as a means by which to better characterize sensory contributions to postural control in the presence of various sensorimotor pathologies, including vestibular hypofunction.